اسلامی جہاد کے اصول و ضوابط اور عصری معنویت (عہدِ خلافتِ راشدہ کے تناظر میں): The Principles of Islamic Jihad and its Contemporary Status (In the context of the Caliphate’s Era) - Liaquat, Dr. Usman; Naimat Ullah, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
Islam gives perfect guidance to man in every sphere of life. There is no aspect of human life that does not have Islamic rules and regulations. From family affairs to da'wah and preaching and the field of jihad, all related etiquette are because of Islam. Islamic law, like other spheres of human life, has laid down rules and regulations to keep war within the realm of civilization and humanity. After carefully examining the etiquette of jihad of the Holy Prophet ﷺ and his appointed commanders and the Rightly Guided Caliphs, the derived rule is: The cause of war would not be a desire but a genuine need. However, when it is not possible to resolve the issue peacefully and there is no other option, then it will be allowed with keeping in consideration the etiquette of killing. "All the war campaigns in the Righteous Caliphate were in fact a continuation of the conquests of the Prophet's time. Key Words: Jihad, War, Holy Prophet ﷺ, Caliphs, Ethics.